Geographic features of road traffic injury in the European region - Kornus, Anatolii; Shyschuk, Volodymyr; Kornus, Olesia (Journal of Education, Health and Sport, 2017)
The number of accidents on the roads, and the death rate from injuries received in the accident, in Europe, much lower than the world at large. However, the problem remains acute and has significant geographical differences and peculiarities, a view which is devoted to this article. It analyzed the number of accidents in Europe due to their level of motorization and the length of the road network. It is the geographic differences in mortality in the context of individual countries and shown her the dynamics within the 2005-2015.